Pelatihan Pengelolaan Administrasi Berbasis Komputer bagi Aparat Kantor Kampung Tulima - Syarifah Syarifah; Nur Aeni; Telly Nancy Silooy; Hasriani M (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
COMPUTER BASED ADMINISTRATION MANAGEMENT TRAINING FOR TULIMA VILLAGE OFFICE OFFICIALS. Administrative management at the Tulima Village Office has so far not been optimal in computer use. This is due to a lack of understanding of computers, as well as a lack of infrastructure in the office. Based on the identification of these problems, the Unaim Yapis Wamena community service team conducted training to provide understanding and knowledge related to the importance of using computers in administrative management. Thus, it will benefit from the ease of managing village administration. The methods used are socialization, practicum assistance, and evaluation. The service was carried out at the Tulima Village Office as Partners consisting of 15 participants. The results of the community service show that Tulima village officials have understood and followed this training activity well. 12 of the 15 participants in this training proved to be able to operate computers well, were able to make letters with Microsoft Word, make tables of incoming and outgoing mail, and simple financial reports. Some of the supporting factors for the implementation of thisactivity include the full support of the Tulima village officials, the openness of the officers about their inability to use computers so that they are easily identified to provide material, as well as the participation and cooperation of the lecturer team. The inhibiting factor for this activity is the limited laptop facilities so it is still not optimal in practicum assistance.